Retracted: Prevalence and Burden of Headache Disorders: A Comparative Regional Study in China. Issue 10 (10th November 2010) - Luo, Ning; Fang, Yannan; Tan, Feng; Zhang, Qian; Zou, Daliang; Cao, Xiutang; Xu, Xuehua; Bai, Hua; Ou, Jiangang; Wu, Haike; Chen, Zilong; Zhou, Yane; et al.
Abstract : Background.— Since the early 1990s, no study has been undertaken examining the prevalence and burden of headache disorders in China. Objective.— We conducted a one‐year survey on the prevalence and burden of primary headache in the Chinese provinces of Guangdong and Guangxi. Our study also evaluated the factors behind similarities and differences affecting prevalence in the 2 regions of study. Methods.— Random samples of 372 local residents in Guangdong and 182 local residents in Guangxi aged 18‐65 years were invited to a face‐to‐face interview. Results.— The one‐year prevalence of primary headache was 22.6% (84/372) in Guangdong and 41.2% (75/182) in Guangxi. The prevalence of migraine (14.3%, n = 26) in Guangxi was higher than prevalence of migraine (8.3%, n = 31) in Guangdong ( P = .03). The ratio of headache cost and household income was 2.1% in Guangdong and 3.7% in Guangxi, the ratio in Guangdong was less than that in Guangxi ( P = .001). The diagnostic confirmation rate of migraine was low. No migraineur used triptans drugs to treat migraine in either region. Conclusion.— Migraine prevalence was higher in the lower‐income region that also contains a higher proportion of ethnic minorities. Although there was no difference of headache cost between the 2 regions, the headache populations in the lower‐income region would relatively suffer a greater financial burden if taking the economic differences between the 2 regions into account. The improvement of diagnostic and therapeutic levels for the treatment of headache, especially migraine, in the 2 regions may be a matter of urgency.